Training of Growth Chart Filling In Puskesmas Gimpu Sigi: Pelatihan Pengisian Kartu Menuju Sehat (KMS) Di Wilayah Kerja Puskesmas Gimpu Kabupaten Sigi - Faisal, Elvyrah; Ansar, Ansar; Basten, Irfan (Jurnal Pengabdian Masyarakat: Svasta Harena, 2021)
This community service aims to improve the knowledge and skills of cadres in filling growth chart in Pilimakujawa, Moa and Lempelero villages in the Gimpu Health Center Work Area, Sigi Regency. The knowledge and skills of cadres in filling out the growth chart are very important and can be assessed based on the accuracy of filling out the growth chart. From the preliminary study obtained information that many cadres who do not know very well how to fill growth chart, especially in remote areas inaccessible region Gimpu Sigi Health Center. The method is carried out using lecture and demonstration methods accompanied by training materials related to filling out the growth chart. This activity is useful because there is an increase in the knowledge and skills of posyandu cadres in filling out growth charts.